Subversion and Desire: Female Body and Sexuality in As malas mulleres (2021), by Marilar Aleixandre (XXI Century. Spanish Literature and Culture, 2024)
This paper studies the presentation of female bodies and sexuality in Marilar Aleixandre's As malas mulleres (2021), a work contextualized in a nineteenth-century Galician women's prison. We contrast the docile and asexual bodies of the submissive inmates with the rebellious and sexually active bodies of Sisca and Fefa, who subvert the femme fatale trope and use their bodies and sexuality as weapons to challenge patriarchal bodily and sexual exploitation. The narrative includes current feminist and LGBTQI demands, denouncing the lack of sexual freedom that still persists in contemporary society.
Keywords: As malas mulleres; Marilar Aleixandre; body; sexuality; prison